Religious morality, secular morality and the search for moral relativism in the west - Campos, Gilvana de Jesus do Vale; Gomes de Lima, Alessandre; Barbas, Stela Marcos de Almeida Neves (Acta Bioethica, 2023)
This work aims to characterize religious and secular moralities in the West from a critical-diachronic point of view,seeking to identify spaces that cover moral relativism in solving complex bioethics issues. Concerns such as the destinationof surplus embryos, for instance, usually raise polarized positionings without consensual solutions. With the presuppositionsintroduced on western culture through several events, mainly the principle of laicity, the view of morality widened. This workis reflexive, meta-ethical, with an interdisciplinary approach. It is a national and international literature review regarding themain points on religious and secular morality. We concluded that the present moral overview certainly includes moral relativismbased on essential morality, one which can be represented by moral strangers and moral friends.